Clonal Restriction of Platelet-associated Anti-GPIIb/IIIa Autoantibodies in Patients with Chronic ITP - McMillan, Robert; Lopez-Dee, Jennifer; Bowditch, Ronald (Thrombosis and Haemostasis, 2001)
Chronic immune thrombocytopenic purpura is due to platelet destruction induced by autoantibodies against platelet surface antigens. Prior studies show that some serum autoantibodies are light-chain restricted, suggesting a clonal origin. Since plasma and platelet-associated antibody from the same patient may bind to different epitopes, it is important to evaluate the clonality of platelet-associated antibody. Platelet-associated autoantibodies from 28 ITP patients were studied. Of 23 platelet-associated antibodies tested directly, 16 showed significant light chain restriction (7 complete and 9 partial) when compared to plasma IgG light chain distribution. Similarly, 9 of 12 platelet-associated antibody eluates were light chain restricted, 5 complete and 4 partial. In all cases where platelet-associated antibody and antibody eluate from the same patient were studied, the results were concordant. We conclude that a significant proportion of platelet-associated antibodies from ITP patients show apparent clonality, as evaluated by light chain restriction. These results are consistent with other studies in ITP suggesting a limited antigenic repertoire.
Keywords: ITP; autoantibody; platelet; clonality